Technology use among Indigenous adolescents in remote regions of Australia - Genevieve Marie Johnson (International Journal of Adolescence and Youth, 2016)
Twenty-four Indigenous adolescents (mean age 16.4 years) attending a boarding school in a remote region of Western Australia participated in individual structured interviews that queried current patterns of use for each of: (1) television, (2) video games, (3) computers, (4) the Internet, and (5) mobile phones. Results suggest that television, video games and computers play a relatively minor role in the lives of participating adolescents. However, the Internet and particularly mobile phones were frequently used. Mobile phones were used by participating Indigenous adolescents in ways consistent with their collective culture (e.g. communicate with family and friends) but also similar to adolescents generally (e.g. to send text messages and access the Internet). When presented with the hypothetical option of using only one small screen technology, Indigenous adolescents overwhelmingly selected a mobile phone. The reasoning for such a preference emphasised the importance of communication and the global functionality of the device (e.g. Internet connectivity). The rapid uptake mobile phones by Indigenous adolescents may point the way to improved educational opportunities, specifically, m-learning.